Electromagnetic shielding behaviors of planar frequency selective surface fabrics, with emphasis on decoupling analysis, lamination direction and tunable selective frequency. (30th June 2022) - Zheng, Yiqian; Wang, Yunyang; Zhu, Chengyan; Wang, Qicai; Qiu, Haibin; Qian, Junnan; Hong, Xinghua
Planar frequency selective surface (FSS) fabrics with grids, strips or patches by simple methods of patching, embroidery, clipping and carving were fabricated. The periodic structures, laminated structures, processing method and materials pertaining to the electromagnetic shielding behaviors were investigated. Firstly, equivalent circuit and electromagnetic (EM) shielding behavior of basic frequency selective structure units and complex fretwork structure were provided, involving the decoupling of complex fretwork structure. In addition, various laminating structures of SPs and SGs were determined, one of superposition of SPs and SGs provides a SE peak of 40.2 dB (average SE of 25.1 dB in the whole frequency domain), the other presents a SE peak of 27.1 dB (average SE of 19.1 dB in the whole frequency regime). Furthermore, tunable selective electromagnetic shielding by a simple mechanical way was provided, which can realize a tunable SE peak varying from 730 MHz to 1580 MHz. This work might provide a perspective for the assemble and analytical approximation of FSS fabrics for scientists and engineers in this cross-disciplinary field.